2016
DOI: 10.1186/s40795-016-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

A 6-month randomised controlled trial investigating effects of Mediterranean-style diet and fish oil supplementation on dietary behaviour change, mental and cardiometabolic health and health-related quality of life in adults with depression (HELFIMED): study protocol

Abstract: Background: Modern diets, characterised by excess consumption of processed foods, are accompanied by an epidemic of chronic diseases. Cardiovascular disease and depression carry a large burden of disease and often occur together. Poor dietary patterns have been identified as an independent risk factor for depression while healthy diets with minimally processed food are protective. Traditional Mediterranean diets have been shown to reduce risk of cardiovascular disease; however there is a need for clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The detailed study protocol is published elsewhere. 18 The trial was registered with the Australian New Zealand Clinical Trials Register (ACTRN12614000438651).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed study protocol is published elsewhere. 18 The trial was registered with the Australian New Zealand Clinical Trials Register (ACTRN12614000438651).…”
Section: Methodsmentioning
confidence: 99%
“…16 Secondary analysis from the PREDIMED study showed some trends for reduced risk of depression in the MedDiet group 17 but was not powered for this outcome. We are aware of only two dietary RCTs in people with depression; this study 18 and another Australian study which was recently completed. 19 Changing established dietary behaviours is challenging, and this is attributed to factors such an obesogenic environment 20 and the addictive nature of high-fat high-sugar foods.…”
Section: Introductionmentioning
confidence: 99%
“…HELFIMED recruited adults with major depression [21], based on a depression diagnosis or at least moderate depressive symptoms for two+ months based on the depression subscale of the Depression Anxiety Stress Scale DASS-21 [22]. At baseline, over 80% of eligible participants reported depressive symptoms in the 'extremely severe' category.…”
Section: Introductionmentioning
confidence: 99%
“…The HELFIMED study protocol describing recruitment strategy, diet and social group conditions and measured outcomes has been published elsewhere [21]. Outcomes were measured at 3-months (end of intervention) and at 6-months (3-month posttrial follow-up).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation